Ca(2+)-Permeable AMPA Receptors Regulate Growth of Human Glioblastoma via Akt Activation - Ishiuchi, Shogo (J Neurosci, 2007)
Evidence has been accumulated that glioblastoma cells release and exploit glutamate for proliferation and migration by autocrine or paracrine loops through Ca(2+)-permeable AMPA-type glutamate receptors. Here, we show that Ca(2+) signaling mediated by AMPA receptor regulates the growth and motility of glioblastoma cells via activation of Akt. Ca(2+) supplied through Ca(2+)-permeable AMPA receptor phosphorylated Akt at Ser-473, thereby facilitating proliferation and mobility. A dominant-negative form of Akt inhibited cell proliferation and migration accelerated by overexpression of Ca(2+)-permeable AMPA receptor. In contrast, introduction of a constitutively active form of Akt rescued tumor cells from apoptosis induced by the conversion of Ca(2+)-permeable AMPA receptor to Ca(2+)-impermeable receptors by the delivery of GluR2 cDNA. Therefore, Akt functions as downstream effectors for Ca(2+)-signaling mediated by AMPA receptor in glioblastoma cells. The activation of the glutamate-AMPA receptor-Akt pathway may contribute to the high degree of anaplasia and invasive growth of human glioblastoma. This novel pathway might give an alternative therapeutic target.